Faktor Penyebab Ketidaklengkapan Pengisian Dokumen Rekam Medis Rawat Inap Rumah Sakit - Azis, Anisya; Alfiansyah, Gamasiano; Wijayanti, Rossalina Adi; Selviyanti, Erna (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The standard for completing medical record documents is 100%, but in some hospitals it is still common to find incomplete filling of medical record documents. So a study is needed that aims to analyze the factors that cause incomplete filling of medical record documents for inpatients at the hospital by using the 5M management elements, namely Man, Materials, Method, Machine, and Money. This study is a literature review of 14 articles obtained from Google Scholar, Garuda, and Crossref. Of the 14 articles reviewed, the causes of incomplete filling in medical record documents for inpatients at the hospital are the lack of discipline of doctors in completing medical records, lack of facilities and infrastructure to support medical record filling, lack of socialization regarding filling out medical record documents, lack of reward and punishment, and limited funds.Keywords: incompleteness; medical records; inpatient; hospital ABSTRAK Standar kelengkapan pengisian dokumen rekam medis adalah 100%, namun pada di beberapa rumah sakit masih sering ditemukan ketidaklengkapan pengisian dokumen rekam medis. Maka diperlukan studi yang bertujuan untuk menganalisis faktor penyebab ketidaklengkapan pengisian dokumen rekam medis pasien rawat inap di rumah sakit dengan menggunakan unsur manajemen 5M, yaitu Man, Materials, Method, Machine, dan Money. Studi ini merupakan literature review terhadap 14 artikel yang didapatkan dari Google Scholar, Garuda, dan Crossref. Dari 14 artikel yang ditelaah, penyebab ketidaklengkapan pengisian dokumen rekam medis pasien rawat inap di rumah sakit adalah kurangnya kedisiplinan dokter dalam melengkapi rekam medis, kurangnya sarana dan prasarana pendukung pengisian rekam medis, kurangnya sosialisasi mengenai pengisian dokumen rekam medis, belum adanya reward dan punishment, dan terbatasnya dana.Kata kunci: ketidaklengkapan; rekam medis; rawat inap; rumah sakit